Facilitators and "deal breakers": a mixed methods study investigating implementation of the Goal setting and action planning (G-AP) framework in community rehabilitation teams - Lesley Scobbie; Edward A. S. Duncan; Marian C. Brady; Katie Thomson; Sally Wyke (BMC, 2020)
Abstract Background High quality goal setting in stroke rehabilitation is vital, but challenging to deliver. The G-AP framework (including staff training and a stroke survivor held G-AP record) guides patient centred goal setting with stroke survivors in community rehabilitation teams. We found G-AP was acceptable, feasible to deliver and clinically useful in one team. The aim of this study was to conduct a mixed methods investigation of G-AP implementation in diverse community teams prior to a large-scale evaluation. Methods We approached Scottish community rehabilitation teams to take part. Following training, G-AP was delivered to stroke survivors within participating teams for 6 months. We investigated staff experiences of G-AP training and its implementation using focus groups and a training questionnaire. We investigated fidelity of G-AP delivery through case note review. Focus group data were analysed using a Framework approach; identified themes were mapped into Normalisation Process Theory constructs. Questionnaire and case note data were analysed descriptively. Results We recruited three teams comprising 55 rehabilitation staff. Almost all staff (93%, 51/55) participated in G-AP training; of those, 80% (n = 41/51) completed the training questionnaire. Training was rated as 'good' or 'very good' by almost all staff (92%, n = 37/41). G-AP was broadly implemented as intended in two teams. Implementation facilitators included - G-AP 'made sense'; repetitive use of G-AP in practice; flexible G-AP delivery and positive staff appraisals of G-AP impact. G-AP failed to gain traction in the third team. Implementation barriers included - delays between G-AP training and implementation; limited leadership engagement; a poor 'fit' between G-AP and the team organisational structure and simultaneous delivery of other goal setting methods. Staff recommended (i) development of training to include implementation planning; (ii) ongoing local implementation review and tailoring, and (iii) development of electronic and aphasia friendly G-AP records. Conclusions The interaction between G-AP and the practice setting is critical to implementation success or failure. Whilst facilitators support implementation success, barriers can collectively act as implementation "deal breakers". Local G-AP implementation efforts should be planned, monitored and tailored. These insights can inform implementation of other complex interventions in community rehabilitation settings.